Islamic Apologetics and Social Construction: Framing Bang Zuma's YouTube Content via James Thrower - Mukhroman, Iman; Halim, Ilim Abdul (International Journal of Nusantara Islam, 2025)
Social media has emerged as a critical arena for religious discourse, reshaping the dynamics of Islamic apologetics in contemporary Indonesia. This study aims to analyze the framing strategies employed in the digital content of Bang Zuma, a popular Muslim apologist on YouTube, particularly known for his polemical videos on Islam-Christianity debates. Drawing upon Robert Entman's framing theory and James Thrower's perspective on the social construction of religion, this research investigates how Bang Zuma’s content contributes to the reconstruction of Islamic identity and discourse within digital spaces. Using qualitative content analysis on three viral video transcripts, the study identifies four key framing strategies: (1) constructing a binary between the "authentic Jesus" and the "false Jesus"; (2) selectively appropriating Biblical texts; (3) positioning Islam as the true heir of monotheism; and (4) delegitimizing Christian theological authority. These strategies not only serve apologetic purposes but also enact a performative reconstruction of Islamic identity tailored to the logic of social media platforms. The findings reveal that Bang Zuma’s digital apologetics represent a transformation of traditional munazara practices, illustrating what Thrower describes as the “reconfiguration of religious authority” in the digital age, where legitimacy is increasingly built through visibility, engagement, and performativity rather than institutional credentials. This study contributes to a deeper understanding of how digital religious actors utilize platform-based affordances to shape public perceptions of Islam, negotiate interfaith boundaries, and reconstruct theological narratives in a fragmented, algorithm-driven media ecosystem.